VP63 National Institute For Health And Care Excellence (NICE) Technology Appraisal Patient Expert Feedback: 15 month analysis. (2017) - Kastoryano, Chloe; Thomas, Lizzie; Livingstone, Heidi; Leng, Gillian
Abstract : INTRODUCTION: The National Institute for Health and Care Excellence (NICE) has a formal policy stating patients, carers and citizens are involved throughout each Health Technology Assessment (HTA). One key way patient/carer organizations are involved is by nominating patient experts to participate in appraisal committee meetings. A NICE 2014 report (1) on Patient Experts experiences identified a need to routinely survey Patient Experts. This has been ongoing since October 2015. This study highlights key findings, including new recommendations and whether previous concerns have been addressed. METHODS: We refined the 2012 survey to be routinely sent to all patient experts that attended a NICE technology appraisal committee meeting. Between October 2015 and December 2016 this online survey was sent to eighty-eight patient experts. After analysis the findings were compared to the previous report to identify whether concerns have been addressed and whether new recommendations should be considered. RESULTS: There was a response rate of 47 percent (n = 41). Quantitative results and qualitative quotes demonstrate that patient experience varies widely. Key findings from the new data revealed that patient experts feel supported by the Public Involvement Programme, however would welcome more opportunities to speak. Notable improvements since 2012 include favourable opinions of support documents and the Chair more regularly introducing themselves to the patient expert before the meeting. Some experts still find the paperwork cumbersome and find the meetings very technical. CONCLUSIONS: Progress has been made since 2012, but further improvements could facilitate even more effective patient involvement. We continue to routinely measure experiences to identify and address evolving issues. Some tensions remain between NICE's remit and processes, and patients expectations of these. The findings, although specific to NICE, hopefully can feed into other patient involvement developments in the wider HTA ecosystem.